2012
DOI: 10.3389/fmicb.2012.00053
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antifungal Activities of New Acylated Derivatives of Epigallocatechin Gallate

Abstract: (−)-Epigallocatechin-3-O-gallate (EGCG) has useful antiviral, antimicrobial, antitoxin, and antitumor properties. Previously, Mori et al. (2008) found that addition of long acyl chains (C16–18) to EGCG enhanced its anti-influenza virus activity up to 44-fold. The chemical stability of EGCG against oxidative degradation was also enhanced by acylation. We further evaluated the in vitro activity spectrum of the EGCG derivatives against a wide range of bacteria and fungi. A series of EGCG O-acyl derivatives were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 44 publications
1
56
1
1
Order By: Relevance
“…In a small prospective cohort study it was reported that gargling with tea catechins extracts was effective in preventing influenza infection in elderly residents of a nursing home (Yamada et al, 2006). In addition, in another randomized, double-blind, placebo-controlled trial, the consumption of catechins for 5 months had a statistically significant preventive effect on clinically defined influenza infection and was well tolerated (Matsumoto et al, 2012). The results of these trials indicate these catechins have a protective effect against influenza virus; however, large-scale studies are needed to confirm this.…”
mentioning
confidence: 99%
“…In a small prospective cohort study it was reported that gargling with tea catechins extracts was effective in preventing influenza infection in elderly residents of a nursing home (Yamada et al, 2006). In addition, in another randomized, double-blind, placebo-controlled trial, the consumption of catechins for 5 months had a statistically significant preventive effect on clinically defined influenza infection and was well tolerated (Matsumoto et al, 2012). The results of these trials indicate these catechins have a protective effect against influenza virus; however, large-scale studies are needed to confirm this.…”
mentioning
confidence: 99%
“…Matsumoto et al, 11 studying the effects of extracts of Camellia sinensis, observed that several bacteria and fungi were sensitive to the extracts. Among them were Escherichia coli and strains of Staphylococcus aureus.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Lodhia et al 12 observed reductions in VSC in vivo immediately after the use of green tea powder, and Zeng and others 13 observed a reduction in the levels of CH 3 SH and H 2 S in vitro after the use of a green tea extract.…”
Section: Introductionmentioning
confidence: 99%
“…The green tea extract inhibited the replication of influenza viruses by preventing acidification of intracellular compartment, such as lysosomes and endosomes (Lee et (Sahaa et al 2010). It has been demonstrated that consumption of catechins for 5 months produced significant inhibitory effects on influenza virus infection, and they were well tolerated (Matsumoto et al 2012). Yang et al (2014) compared in vitro antiviral activity of various components of green tea in influenza virus A and B.…”
Section: Influenza Virusmentioning
confidence: 99%